On line and double integrals in the non-Newtonian sense - Cakmak, Ahmet Faruk; Basar, Feyzi (AMER INST PHYSICS, 2014)
This paper is devoted to line and double integrals in the sense of non-Newtonian calculus (*-calculus). Moreover, in the sense of *-calculus, the fundamental theorem of calculus for line integrals and double integrals are stated and proved, and some applications are presented.
Keywords: Non-Newtonian calculus; Non-Newtonian line integral; Non-Newtonian double integral; CALCULUS; Mathematics; Physics